Analisis Pengaruh Rasio Keuangan Setelah Merger Terhadap Kinerja Keuangan Perusahaan Pada PT Indosat Tbk - Latresia Aprilia Br. Sitepu; Tiar Natalia Simarmata; Ratih Kusumastuti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This study examines the effect of financial ratios after the merger of PT Indosat Tbk on the company's financial performance. By analyzing the company's financial report data using financial ratios, you can see changes in the financial performance of a business after the merger with PT Hutchison Tri Indonesia. The information including the data needed in this study was taken through the official website of the Indonesia Stock Exchange (IDX). on the website www.idx.co.id and the official website of PT Indosat Tbk on the site www.ioh.co.id so that this research can be carried out. The ratio of liquidity, solvency, profitability and activity is the ratio used to analyze the financial ratios of the company. The liquidity ratio and solvency ratio of PT Indosat Tbk experienced an increase after the merger, while the profitability ratio and activity ratio did not significantly affect the company.